Final examination time table scheduling using integer programming with average time slot gap minimization - Nur Hidayah Abdul Jamil,; Nor Aliza Ab Rahmin,; Athirah Nawawi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The exam of scheduling problem is an academically researched type of scheduling challenge in which exams for a given number of courses are assigned to specific time slots subject to certain constraints. The problem arises when there is a conflict or redundant examination in a time slot of the day. In this research, our aim is to maximize the total amount of students’ study time to ensure that all students have sufficient time to study during exam weeks. We used an integer programming approach with an average time slot over the examination for this examination scheduling problem. The algorithm is applied to real data from third-year students of Bachelor of Science in Mathematics with Honours at the Department of Mathematics and Statistics, Faculty Science, UPM during semester 2 session 2021/2022. The result shows that integer programming gives an optimal solution for this complexity. With some improvements to the algorithm, there can be solutions that are better than the manually compiled schedule.